Management of Large Facial Patch With Recurring Reversal Reaction: A Case Report (Journal of Chittagong Medical College Teachers' Association, 2014)
Inflamed large facial patch, being compromising the appearance and beauty of a patient, is a source of embarrassment and distress, and affects anti-leprosy drive adversely in many ways in the field situation. Its management with oral prednisolone alone, the mainstay of treatment for reversal reaction, proved disappointing. To see whether topical tacrolimus will be helpful in managing those patients. We treated a patient with recurring reversal reaction in large facial patch with tacrolimus 0.1% ointment, twice daily and lower dose oral prednisolone for twelve months during March, 2012-February, 2013. Complete remission was achieved No side effects of whatsoever was seen. No recurrence of reaction is seen till to date. Tacrolimus ointment and lower dose prednisolone was found helpful in managing patient with recurring reversal reaction in large facial patch.JCMCTA 2014 ; 25 (2) : 65-68